Has Family Leave Legislation Increased Leave-Taking? - Charles L. Baum (Washington University Journal of Law & Policy, 2004)
In 1993, the federal government passed the Family and Medical Leave Act (FMLA), which gives eligible employees twelve weeks of job-protected unpaid leave from work per year to address family issues. Employees are eligible for family leave under the FMLA if they have worked for their employer for at least a year, accumulating at least 1,250 work hours. Employers are covered if they employ at least fifty workers. Prior to the FMLA’s passage, twelve states and the District of Columbia had passed their own family leave legislation mandating similar benefits. One potential use of family leave legislation is to give mothers leave from work after giving birth. One potential use of this legislation is to allow mothers leave from work after giving birth. In this Essay, I estimate the effects of family leave legislation on mothers’ leave-taking after giving birth. I examine the effects of family leave legislation as a natural experiment because state family leave laws (passed prior to the FMLA) vary both in scope and in dates of enforcement. I also identify the mothers who have the employment history to be eligible for the mandated leave benefits and who work for employers of sufficient size to be covered by their state’s legislation. My results suggest that family leave legislation has had little effect on leave-taking.
Keywords: Parental leave; Social sciences; Families; Employment